Chinese Indentured Labour in the Dutch East Indies, 1880–1942 Tin, Tobacco, Timber, and the Penal Sanction - Benton, Gregor (Palgrave Macmillan Transnational History Series, 2022)
XXII, 611 p. 8 illus.